Outcome of Management of Malignant Pleural Effusion by Tube Thoracostomy and Chemical Pleurodesis - Study of 282 Cases - Rahman, MS; Uddin, MN; Islam, MA; Rahman, MA; Majumdar, MNI (Journal of Armed Forces Medical College, Bangladesh, 2013)
DOI: http://dx.doi.org/10.3329/jafmc.v8i2.16356 JAFMC Vol.8(2) 2012 pp.58-63